2012
DOI: 10.3923/pjbs.2012.854.862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lead Nitrate on the Liver of the Cichlid Fish (Oreochromis niloticus): A Light Microscope Study

Abstract: The adverse impacts of heavy metals on fish liver were evident with great variability among organs and species. The present study deals with the histological changes of the hepatocytes of the Nile tilapia, Oreochromis niloticus, following exposure to 2.5, 5, 10 ppm of lead nitrate for 1, 2, 3, 4 weeks. The present results revealed that lead nitrate exerts some histological effects on the hepatic tissue after exposure to the first concentration in the form of dilatation and congestion of the blood vessels, vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Despite the role of liver in heavy metal detoxification (Heath, 1995), few studies have described the effects of acute Pb toxicity on liver histopathology in fish. As was observed in R. quelen, Suiçmez et al (2006) reported venous congestion and hepatocytes necrosis in Oncorhynchus mykiss (Walbaum) exposed to 10 mg l À 1 Pb for 72-h. After 7 days of exposure to the same concentration, Khdir et al (2012) only observed an increase of hepatocyte vacuolization in O. niloticus.…”
Section: Discussionmentioning
confidence: 79%
“…Despite the role of liver in heavy metal detoxification (Heath, 1995), few studies have described the effects of acute Pb toxicity on liver histopathology in fish. As was observed in R. quelen, Suiçmez et al (2006) reported venous congestion and hepatocytes necrosis in Oncorhynchus mykiss (Walbaum) exposed to 10 mg l À 1 Pb for 72-h. After 7 days of exposure to the same concentration, Khdir et al (2012) only observed an increase of hepatocyte vacuolization in O. niloticus.…”
Section: Discussionmentioning
confidence: 79%
“…Glycogen depletion has been reported in liver fishes, after short and long term exposure to other heavy metals, such as copper, cadmium and lead [ 48 , 50 , 51 ]. Moreover, similar glycogen perturbations have also been recorded in both liver and muscle of Oreochromis mossambicus as result of mercury chloride toxicity; Roy George and colleagues [ 27 ] suggested that the great loss of glycogen in the liver indicates that it is the most affected organ during stress.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous reports on Oreochromis niloticus when chronically exposed to high Pb concentrations [33,61], the first and most frequent alteration observed in D. rerio liver was the congestion of blood vessels and sinusoids. Such circulatory alterations have been regarded as reversible modifications that do not alter the normal function of the tissue [59], leading us to suppose that a recovery of the health status would be possible if the input of the toxicant ceased.…”
Section: Morphological Modificationsmentioning
confidence: 93%